Covira: A COVID-19 risk assessment, visualization and communication tool - Bhoj Raj Ghimire (Elsevier, 2021)
Assessing the possibility of Coronavirus infection and its risk on an individual’s life, estimating the spatial transmission risk based on the dynamic condition of a particular place into consideration, and communicating the same to the public is crucial for minimizing the potential impact of COVID-19. With the increase in cases world-wide, new patterns are being unfolded. Nevertheless, an application for risk assessment will not only help the researcher to quickly verify the proof of concept but also is a powerful tool to bring into notice the results immediately as one of the perfect tools for risk communication. Covira (https://covira.info) is an open-source web-based software that captures the response, calculates personal as well as regional risk, and displays the result to the end-user in the form of maps and risk cards.